Academic Motivation of Highschoolers During Distance Learning: The Contribution of Perceived Social Support and Grit: [Motivasi Akademik Siswa SMA yang Menjalani Pembelajaran Jarak Jauh: Sumbangan Persepsi Dukungan Sosial dan Grit] - Salim, Rose Mini Agoes; Ginandra, Regia Lidwina; Rumalutur, Nur Aisyah (Faculty of Psychology, Universitas Surabaya, 2023)
The changing in learning activities from face-to-face classes to distance learning has brought a decrease in student’s enthusiasm and involvement. This change might also cause a decrease in academic motivation among high school students. Academic motivation could be increased by internal factors, namely perceptions of social support and grit. This study aimed to examine the contribution of perceived social support and grit on academic motivation. This study’s measurements utilized: (1) the Academic Motivation Scale (AMS) for academic motivation; (2) Social Provisions Scale (SPS) for perceived social support; and (3) Grit Short Scale (GRIT-S) for grit. Data was obtained using a series of questionnaire distributed online. This study involved total of 222 high school students undergoing distance learning. Based on a multiple linear regression analysis, it was found that perceived social support and grit had a significant contribution of 8.7% to academic motivation (F = 10.392; R² = .087; Adjusted R² = .078; p = .05). Therefore, related parties need to maintain and develop social support and grit for students so that academic motivation can remain good even when faced with distance learning conditions. Perubahan kegiatan belajar menjadi pembelajaran jarak jauh (PJJ) membawa berbagai perubahan yang dapat menyebabkan menurunnya semangat dan keterlibatan, karena menurunnya motivasi akademik pada siswa sekolah menengah atas (SMA). Motivasi akademik dapat ditingkatkan dengan faktor internal, yaitu persepsi terhadap dukungan sosial dan grit. Studi ini ingin melihat kontribusi dari persepsi terhadap dukungan sosial dan grit secara bersamaan pada motivasi akademik. Pengukuran variabel studi ini dilaksanakan menggunakan: (1) motivasi akademik dengan Academic Motivation Scale (AMS); (2) persepsi terhadap dukungan sosial dengan Social Provisions Scale (SPS); dan (3) grit dengan Grit Short Scale (GRIT-S). Data studi ini didapatkan dengan menggunakan kuesioner yang disebarkan secara daring. Sebanyak 222 partisipan yang sedang menjalani pembelajaran jarak jauh (PJJ) dilibatkan dalam studi ini, dan berdasarkan analisis multiple linear regression, didapatkan hasil bahwa persepsi terhadap dukungan sosial dan grit secara bersamaan memiliki kontribusi yang signifikan senilai 8,7% terhadap motivasi akademik (F = 10,3; R² = 0,087; Adjusted R² = 0,078; p < 0,05). Maka dari itu, penting bagi pihak terkait untuk menjaga dan mengembangkan dukungan sosial dan juga grit pada siswa agar motivasi akademik dapat tetap baik walaupun dihadapkan pada kondisi pembelajaran jarak jauh (PJJ).